A comparative paper on measuring the performance of snort and suricata with variable packet sizes and speed - Naga Surya Lakshmi, M.; Y. Radhika, Dr. (International Journal of Engineering and Technology, 2019)
This survey paper focuses mainly on comparing the performance of free open-source IDS tools like snort and Suricata, for identifying malignant activities on HIDS. Among the existing intrusion detection tools, Snort is one of the best free open-source tools and for over a decade it is the most widely used tool in the computing industry. The objective of Suricata is to offer signature-based intrusion detection and the latest version is released in the year 2018. Suricata is combined with the latest advancements in recent technology such as multi-threading of the process in order to get better processing rate. We evaluated the processing speed, consumption of memory, and accuracy. We observed in the process of handling a larger amount of network traffic data Suricata has shown better results when compared with Snort and both tools have registered with like accuracy.Â